Betalactam hypersensitivity: The importance of delabelling in primary care. Issue 12 (14th May 2021) - Ben Fadhel, Najah; Aroua, Fares; Chadli, Zohra; Ben Romdhane, Haifa; Chaabane, Amel; Sahtout, Mounira; Boughattas, Naceur A.; Ben Fredj, Nadia; Aouam, Karim
Abstract : Patients and methods: An allergy work‐up was performed on adult patients with a history of a penicillin allergy seen by primary medical care in Monastir (Tunisia) between July 2016 and February 2018. Patients with negative skin tests were challenged with amoxicillin. Patients who were delabelled were contacted by phone after 6 months to determine outcomes after any therapeutic penicillin‐class antibiotic intake. Results: A total of 39 patients were evaluated and 33 (84.6%) were delabelled. Five patients were penicillin skin‐test positive and one was oral challenge positive. We succeeded in contacting 33 delabelled patients at 6 months. Twenty‐two patients tolerated a subsequent therapeutic course of amoxicillin, eight patients did not retake penicillin due to a lack of therapeutic indication, and three patients refused an indicated penicillin use fearful of another reaction. Conclusion: This study highlights the importance of allergy work‐up in the diagnosis of beta‐lactam hypersensitivity. Most patients were excessively labelled as beta‐lactam allergic and this mislabelling could increase healthcare costs and lead to the development of drug resistance by the use of wide‐spectrum antibiotics